English Conversation Teaching by Pair-work Technique for the First Year English Majored Students - Muhammad Dalimunte (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study discusses about English conversation teaching by pair-work technique for the firts year English majored students. This study uses Classroom Action Research. It can be used to know the improvement of teachers’ activity and students’ ability after a particular technique applied. The research findings denoted that pair-work technique can attract the students’ motivation to take part in language teaching and improve their ability at speaking, It can seen from the improvement of students’ activities from cycle one to cycle two  (82,5 % of the students took part in the teaching -learning process or at  level 3,3 ,good category to 91,25% or at the level 3,65, good category in cycle two, and the improvement of their scores  was 7 students (21,9%) got score 70 up in pre cycle, 29 students  (90,6 %) in cycle one and 32 students (100%)  in cycle two. It can be stated that the pair-work technique is appropriate to apply in teaching speaking.